Microneedling dilates the follicular infundibulum and increases transfollicular absorption of liposomal sepia melanin - Serrano G; Almudéver P; Serrano JM; Cortijo J; Faus C; Reyes M; Expósito I; Torrens A; Millán F (Dove Medical Press, 2015)
Gabriel Serrano,1 Patricia Almudéver,2 Juan M Serrano,3 Julio Cortijo,2 Carmen Faus,1 Magda Reyes,1 Inmaculada Expósito,3 Ana Torrens,3 Fernando Millán1 1Clínica Dermatológica Serrano, 2Department of Pharmacology, University of Valencia, 3Research and Development Department, Sesderma Laboratories, Valencia, Spain Abstract: Encapsulation of chemicals in liposomes and microneedling are currently used techniques to enhance the penetration of several substances through skin and hair. In this study, we apply a liposomal melanin–fluorescein compound to an ex vivo model of human skin, using a new electrical microneedling device (Nanopore turbo roller). The product was applied by hand massage (A) or with the assistance of the electrical roller for 2 minutes (B). An additional test was performed free of product and with only the E-roller (C). Histological changes and product absorption were evaluated by optical and fluorescent microscopy 60 and 90 minutes after the treatment. Site B showed larger deposits of melanin–fluorescein at superficial and deep levels of hair structures in comparison to site A. Light, epidermal deposits of the melanin–fluorescein complex were also observed. Sites B and C showed a significant widening (47%) of the follicular infundibulum which could explain the increased penetration of the formulation. Microneedling also removed the scales and sebum residues in the neighborhood of the infundibulum. Targeting hair follicles with melanin may be useful to dye poorly pigmented hairs, improving laser hair removal. The procedure accelerates the delivery of melanin into hair structures allowing an even absorption, larger pigment deposits, and deeper penetration of the formulation into the hair. Keywords: liposomes, melanin, microneedling, follicular infundibulum, hair removal